Clinicopathological features of Pseudocyst Pancreas and its Management: A Prospective and Retrospective Study - Dr. Mahim Koshariya; Dr. Agam Sharma; Dr. Brahmanand Gupta; Dr. Tushar Suroshe; Dr. Jaiprakash Singour; Dr. M C Songra (Surgical Review: International Journal of Surgery, Trauma and Orthopedics, 2021)
Background: Revised Atlanta Classification has veered a change in our understanding of pseudocyst pancreas which mandates renewed inquiry into pseudocysts defined as per new criteria. The present study provides an overview of experience with Pseudocyst Pancreas for over a decade. Methodology: 100 cases of pseudocysts diagnosed over the last 10 years at GMC, Bhopal, conforming to the present definition were reviewed. Cysts with the inhomogeneous collection, debris, necrosis, or any other non-liquid component, specifically in those diagnosed before 2012 were excluded. Relevant data were analyzed. Results: The majority were male (85%) in the age group of 40-50 years with alcohol-induced chronic pancreatitis (77%) being the most frequent etiology. Abdominal pain (40%), lump (30%), and abdominal tenderness (59%) were common at presentation. 58% were in the Head of the pancreas, 29% in the Neck and Body, and 13% in the Tail and surrounding areas. Mean cyst diameter was 8.6cm and volume 252cc. 85% were managed surgically and 40% of those managed conservatively also needed surgical intervention eventually due to complications. History of chronic alcoholic pancreatitis, the large size of the cyst (≥6cm and ≥60cc), and communication with the main pancreatic duct were highly predictive of surgical intervention. Conclusion: Radiological characteristics along with the clinical picture may suggest appropriate intervention. Surgery remains the principal modality of treatment, with high success rates.